Investigation of Hemispherical Resonator for and Energy Store; Radioelectronics and Communications Systems; Vol. 30, № 2 - Avgustinovich V. A.; Avgustinovich L. Y.; Artemenko S. N.; Yushkov Y. G. Yuri Georgievich (1987, 1987)
High-power microwave pulses can be generated by the slow storage of energy in a resonant cavity, and the subsequent discharge of this energy in a time interval much less than the storage time. The amplitude of the radio pulse obtained depends on the volume of the cavity, its Q, the stored energy density, and the nature of the operation of the switching device. The simplest method of increasing the level of stored energy in the resonant system is to increase its volume while simultaneously choosing the optimum geometry. We give some results of an investigation of a superdimensional hemispherical copper resonator for the purpose of using it as an energy store when generating microwave pulses